Statistical analysis of test methods to evaluate rendering surface properties - Carasek, Helena; Vaz, Fernando Henrique; Cascudo, Oswaldo (Ambiente Construído, 2018)
The objective of this study is to discuss the results of two test methods used to evaluate rendering surface properties: the superficial tensile strength (STS) and the pendulum rebound hammer (which provides the rebound index – RI), besides evaluating, additionally, the tensile bond strength (BS). The studied variables were the type of mortar (job-site mortar and dry-mix mortar) and the render moisture at the time of testing (in four contents). For each test, a minimum of 45 determinations was planned per analyzed situation, totaling 1411 valid results, which allowed a consistent statistical analysis and an in-depth discussion of the methods. The STS and RI tests were sensitive at a 95% confidence level to differentiate mortars from different strengths and were therefore approved for this evaluation. The most significant effect in all statistical models tested was the type of mortar. The variable moisture condition of the render was significant only for the results of STS and BS. In such cases, tests performed with wet or saturated renders presented much lower strength results compared to those carried out with air- dried renders. It was possible to obtain a significant correlation between STS and BS, with a high coefficient of determination.